Salmonella Neck Abscess: A Case Report (Journal of Chittagong Medical College Teachers' Association, 2010)
Due to errors in this paper, a corrected version is reprinted in Vol.20(2) 2009 p.51-52.Key words: salmonella; abscess; neck DOI: 10.3329/jcmcta.v20i1.4939 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):61-63